2018
DOI: 10.1016/j.nbd.2018.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine has two faces: Regionally dichotomous adenosine tone in a model of epilepsy with comorbid sleep disorders

Abstract: This is the first study to demonstrate a direct correlation of regionally distinct dichotomous adenosine levels in a single model with both epilepsy and comorbid sleep disorders. The weaker inhibitory tone in the dorsal hippocampus is consistent with lower seizure threshold, whereas increased adenosine in the LH is consistent with chronic partial sleep deprivation. This work furthers our understanding of how adenosine may contribute to pathological conditions that underlie sleep disorders within the epileptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…It is hypothesized that a decreased adenosine tone uniformly forms the base for both epilepsy and sleep disruption (90). However, recent study found a lineal association of regionally distinguishable dichotomous levels of adenosine in one model represent both epilepsy and comorbid sleep disorders (110). In the model, adenosine level was decreased in the dorsal hippocampus contributing to seizure threshold diminution, while adenosine level was increased in the lateral hypothalamus leading to chronic partial sleep deprivation.…”
Section: Adenosine Dysfunction In Comorbidities Associated With Epilepsymentioning
confidence: 99%
“…It is hypothesized that a decreased adenosine tone uniformly forms the base for both epilepsy and sleep disruption (90). However, recent study found a lineal association of regionally distinguishable dichotomous levels of adenosine in one model represent both epilepsy and comorbid sleep disorders (110). In the model, adenosine level was decreased in the dorsal hippocampus contributing to seizure threshold diminution, while adenosine level was increased in the lateral hypothalamus leading to chronic partial sleep deprivation.…”
Section: Adenosine Dysfunction In Comorbidities Associated With Epilepsymentioning
confidence: 99%
“…Adenosine levels increase during wakefulness and are depleted during sleep (163, 168). The sleep disturbances often associated with epilepsy may be explained by alterations in adenosine signaling (169). Adenosine is an endogenous anticonvulsant and adenosine levels increase during seizures (170, 171).…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Furthermore, manipulations to adenosine or its clearance modulate epileptogenesis (171173). Having recurrent seizures may, in turn, decrease, or increase adenosine levels in different brain areas (169). Adenosine analogs applied to the brainstem of rats cause prolonged suppression of breathing (174, 175).…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Excessive increases in extracellular adenosine suppress neuronal activity and may contribute to PGES and the postictal state (Rosen and Berman, 1985;During and Spencer, 1992). Though acute seizures cause an increase in extracellular adenosine, chronic epilepsy is associated with a reduction of baseline adenosine levels, which could be a precipitating factor in epileptogenesis (Gouder et al, 2004;Li et al, 2008) and associated co-morbid conditions including cognitive, psychiatric, and sleep disorders (Yee et al, 2007;Boison et al, 2012;Shen et al, 2012;Boison, 2016;Warren et al, 2018). Spreading depolarization waves, which can occur during seizures, result in a prolonged increase in extracellular adenosine Abbreviations: 5-ITU, 5-iodotubercidin; A 1/2A , adenosine receptor; ADK, adenosine kinase; ATP, adenosine triphosphate; DPCPX, A 1 receptor antagonist; dnSNARE, N-ethylmaleimide-sensitive factor attachment protein receptor; EEG, electroencephalogram; EKG, electrocardiogram; EHNA, erythro-9-(2-hydroxy-3-nonyl)-adenine hydrochloride; GEPR-9s, genetically epilepsy-prone rats; GRAB Ado , GPCR-activation based adenosine sensor; PGES, postictal generalized EEG suppression; SCH 442416, A 2A receptor antagonist; SUDEP, sudden unexpected death in epilepsy.…”
Section: Introductionmentioning
confidence: 99%